Iron isotopes reveal the sources of Fe-bearing particles and colloids in the Lena River basin. (15th January 2020) - Hirst, Catherine; Andersson, Per S.; Kooijman, Ellen; Schmitt, Melanie; Kutscher, Liselott; Maximov, Trofim; Mörth, Carl-Magnus; Porcelli, Don
Abstract: Large Arctic rivers are important suppliers of iron to the Arctic Ocean. However, the sources of Fe-bearing particles in permafrost-dominated systems and the mechanisms driving this supply of Fe are poorly resolved. Here, Fe isotope ratios were used to determine the sources of Fe-bearing particles and colloids in the Lena River and tributaries. In samples collected after the spring floods, Fe-bearing particles (>0.22 µm) carried ∼70% of the Fe and have isotope ratios that are lower than, or similar to that of the continental crust. These particles are composed of a leachable Fe fraction of largely ferrihydrite, with isotope values of −1.40‰ to −0.12‰, and a fraction of clays and Fe oxides with continental crust values. Co-existing Fe-bearing colloids (<0.22 µm), composed mainly of ferrihydrite, have higher isotope values, of −0.22‰ to +1.83‰. A model is proposed in which soil mineral weathering generates aqueous Fe with lower δ 56 Fe values. During transport, a small fraction of the dissolved Fe is precipitated as colloidal ferrihydrite with higher δ 56 Fe values. Most of the Fe is precipitated onto mineral grains in oxic riparian zones, with the δ 56 Fe values largely generated during weathering. Groundwater discharge and riparian erosion supply the colloids and coated particles to the rivers. The differences between δ 56 Fe values in leachates and detrital grains in Fe-bearing particles agree with values determined in mineral dissolution experiments and in Fe accumulation horizons in soils. The difference in δ 56 Fe values between leachates and colloids reflects isotope fractionation during incremental Fe(III)aq precipitation and Fe-OC complexation during transport towards the riparian zone. Overall, the Fe isotope values of riverine particles and colloids reflect processes that occur during mineral dissolution, transport, and secondary mineral formation in permafrost soils.